Forms of Services, Effectiveness, and Obstacles in Conducting Digital- Based Land Registration in The Era of Digitalization at Lembata Regency Land Office, East Nusa Tenggara Province - Sherly Anggriany De Haan (Journal of Digital Law and Policy, 2023)
Entering the digital era, the Ministry of Agrarian and Spatial Planning/National Land Agency (BPN) has launched land services electronically. The implementation of land registration is carried out electronically, this is stated in Article 2 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning / National Land Agency (ATR / BPN) Number 1 of 2021 concerning Electronic Certificates. This is a series of digital transformations that are rolling out at the Ministry of ATR / BPN. However, there are still many plots of land for which physical data and juridical data are not yet available. This study investigates digital-based land registration services at the Land Office of Lembata Regency, focusing on their various forms, effectiveness, and obstacles to successful implementation. The research method was empirical, involving the collection of primary and secondary data through interviews and descriptive analysis. The study identified three main forms of digital-based land registration services: Electronic Dependent Rights Services, Electronic Roya Services, and Certificate Checking. However, these services have not been fully effective due to obstacles such as incomplete data validation, lack of human resources, and inadequate socialization and communication about digital-based services.